Resolving vibrations in a polyatomic molecule with femtometer precision via x-ray spectroscopy - Rupprecht, Patrick; Aufleger, Lennart; Heinze, Simon; Magunia, Alexander; Ding, Thomas; Rebholz, Marc; Amberg, Stefano; Mollov, Nikola; Henrich, Felix; Haverkort, Maurits W.; Ott, Christian; Pfeifer, Thomas (Physical review, 2023)
We measure molecular vibrations with femtometer precision via resonance energy shifts using time-resolved x-ray absorption spectroscopy. For a demonstration, a Raman process excites the A1g mode in gas-phase SF6 molecules with an amplitude of approximately 50fm, which is probed by a time-delayed soft-x-ray pulse at the sulfur L2,3 edge. Mapping the extremely small measured energy shifts to internuclear distances requires an understanding of the electronic contributions provided by a many-body ab initio simulation. Our study establishes core-level spectroscopy as a precision tool for time-dependent molecular-structure metrology.
Gesehen am 05.12.2023